Agglomeration, Spatial Interaction and Convergence in the EU - Michael Bräuninger; Annekatrin Niebuhr (Hamburg Institute of International Economics (HWWA), 2005)
We investigate the convergence process among EU regions between 1980-2002 taking into account the effects of spatial heterogeneity and spatial spillover effects. The spatial regimes model allows for different steady-state growth paths. In contrast to previous analyses, the regimes in this paper refer to spatial categories, i.e. we assume that agglomerations, urbanised and rural regions are characterised by group-specific steadystates. Moreover, the regression analysis considers the effects of interaction among neighbouring regions, possibly leading to a spatial dependence of regional growth rates. We check whether spatial dependence is caused by spatial spillovers or based on country effects.
Keywords: O52; R11; C21; 330; Convergence; agglomeration; European Union; spatial econometrics; quantile regression; Entwicklungskonvergenz; Räumliche Interaktion; Regionales Wachstum; EU-Staaten